In search of now : the science of the present moment - Marchant, Jo, 1973- (Liveright Publishing Corporation, a division of W. W. Norton & Company, 2026)
"[The author] takes us on a grand tour of the latest thinking in cosmology, quantum mechanics, psychology, and neuroscience to ... explore the fundamental essence of time"--Flap page 1 of dust jacket.